Impact of CYP2C19 Metabolizer Status on Patients With ACS Treated With Prasugrel Versus Clopidogrel - Doll, Jacob A.; Neely, Megan L.; Roe, Matthew T.; Armstrong, Paul W.; White, Harvey D.; Prabhakaran, Dorairaj; Winters, Kenneth J.; Duvvuru, Suman; Sundseth, Scott S.; Jakubowski, Joseph A.; Gurbel, Paul A.; Bhatt, Deepak L.; et al. (Journal of the American College of Cardiology, 2016)
Certain alleles of the CYP2C19 gene are associated with higher platelet reactivity and increased ischemic events among patients treated with clopidogrel. However, the relationship of CYP2C19 genotype and outcomes in medically managed patients with acute coronary syndromes (ACS) is not known. This study sought to assess the effect of CYP2C19 genotype on ischemic outcomes in patients with ACS initially managed medically without revascularization who were randomized to either clopidogrel or prasugrel. We classified patients as extensive metabolizers (EM) or reduced metabolizers (RM) based on CYP2C19 genotype and evaluated ischemic outcomes and platelet reactivity. Among 9,326 patients enrolled from 2008 to 2011, 5,736 participated in the genetics cohort; of these, 2,236 had platelet function testing data. There was no association between CYP2C19 metabolizer status (EM vs. RM) and the primary composite endpoint of cardiovascular death, myocardial infarction (MI), or stroke (hazard ratio [HR]: 0.86). EM and RM patients had similar rates of the primary endpoint whether treated with prasugrel (HR: 0.82) or clopidogrel (HR: 0.91; p for interaction = 0.495). After adjusting for clinical and treatment variables, EM patients had a lower risk of MI versus RM patients (HR: 0.80), but risks of other outcomes were similar. RM patients had significantly higher mean P2Y12 reaction units versus EM patients when treated with clopidogrel (39.93), but not with prasugrel (3.87). CYP2C19 metabolizer status is not associated with the composite outcome of cardiovascular death, MI, or stroke in medically managed ACS patients treated with clopidogrel or prasugrel. Our findings do not support routine CYP2C19 genetic testing in this population. (A Comparison of Prasugrel and Clopidogrel in Acute Coronary Syndrome Subjects [TRILOGY ACS]; NCT00699998)